Suits. Season six [videorecording (DVD)] - Macht, Gabriel, 1972-; Adams, Patrick J., 1981-; Hoffman, Rick, 1970-; Meghan, Duchess of Sussex, 1981-; Torres, Gina (Universal Pictures Home Entertainment, 2017)
After signing a plea deal to spare his colleagues at Pearson Specter Litt, Mike faces the harsh realities of prison life as he starts his two-year sentence. Meanwhile, the once bustling PSL offices are now a ghost town. The partners have defected, leaving Harvey, Jessica, Louis, Donna, and Rachel to pick up the pieces. With the firm facing numerous lawsuits as fallout of the plea deal, and Harvey on a mission to get Mike released from prison, PSL's troubles are far from over.